Styling blackness in Chile : music and dance in the African diaspora - Wolf, Juan Eduardo, 1971- (Indiana University Press, 2019)
In Styling Blackness in Chile, Juan Eduardo Wolf explores the multiple ways that Black individuals in Arica have performed music and dance to frame their Blackness in relationship to other groups of performers--a process he calls styling.